Macronutrientes no cultivo e rendimento de óleo essencial de ocimum basilicum l. - Lima, Janderson do Carmo (2021)
The cultivation of basil has attracted the interest of many pharmaceutical and gastronomic companies. This is because it is a medicinal plant with excellent potential for the production of essential oils, in addition to composing several dishes of the local cuisine, however, it is still an underutilized species despite its great genetic potential, as information about its nutritional requirements is a limiting factor to your cultivation. This work aimed to characterize the influence of different concentrations of macronutrients on growth, nutritional diagnosis and production of essential oils in O. basilicum plants cultivated in a dystrophic Yellow Argisol. The experiment was carried out in a greenhouse and the treatments consisted of a reference dose determined from several scientific articles, with the others determined from this reference level in the Baconian matrix scheme, where only the indicated nutrient varied in dose. 100 plants were used in polyethylene pots with a capacity of 6 dm-3. At 50 days after transplanting the basil seedlings, the growth evaluations were carried out. A significant effect on phytomass production was observed as a function of all nutrients tested, highlighting that basil plants are very demanding in N, which is the most requested element and with more variations in the estimated doses. The ideal maximum accumulation of N and P in basil leaves for full plant performance is 51 and 3.0 g kg-1 respectively. The maximum P accumulation in basil plants when cultivated in Dystrophic Yellow Argisol was 7.9 g kg-1. And for the extraction of essential oils, samples of dry phytomass from the leaves (previously dehydrated at 45ºC) were used, being carried out via hydrodistillation by steam drag in a Cleverger apparatus. Nitrogen fertilization at 75 mg dm-3 promoted the highest essential oil yield and productivity in basil plants.